2017
DOI: 10.1104/pp.17.00834
|View full text |Cite
|
Sign up to set email alerts
|

Different Routes for Conifer- and Sinapaldehyde and Higher Saccharification upon Deficiency in the Dehydrogenase CAD1

Abstract: In the search for renewable energy sources, genetic engineering is a promising strategy to improve plant cell wall composition for biofuel and bioproducts generation. Lignin is a major factor determining saccharification efficiency and, therefore, is a prime target to engineer. Here, lignin content and composition were modified in poplar (Populus tremula 3 Populus alba) by specifically down-regulating CINNAMYL ALCOHOL DEHYDROGENASE1 (CAD1) by a hairpin-RNA-mediated silencing approach, which resulted in only 5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 122 publications
(202 reference statements)
12
116
0
1
Order By: Relevance
“…There have been reports on enhanced saccharification from CAD mutant biomasses (11,(39)(40)(41). It is challenging to directly compare the results from these different studies with the present study because the biomass is derived from different plant species that have various levels of both lignin and CAD deficiency.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…There have been reports on enhanced saccharification from CAD mutant biomasses (11,(39)(40)(41). It is challenging to directly compare the results from these different studies with the present study because the biomass is derived from different plant species that have various levels of both lignin and CAD deficiency.…”
Section: Discussionmentioning
confidence: 95%
“…It is challenging to directly compare the results from these different studies with the present study because the biomass is derived from different plant species that have various levels of both lignin and CAD deficiency. However, it would be interesting to test and scale-up DES-based pretreatment process with biomass from CAD-deficient bioenergy crops such as poplar (11), bm1 maize (47), bm6 sorghum (48), and switchgrass (49). It is worth noting that, unlike certain mutants affected in other steps of the lignin biosynthetic pathway, several CAD mutants do not show any visible phenotype or biomass yield penalty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo this results in the presence of an unsaturated bond between carbons 7 and 8 in the 8-O-4 and 8-8 linkages [52]. Multiple studies have shown that CAD mutation or downregulation reduces recalcitrance or increases extractability of hemicelluloses or lignin, but any reduction in hemicellulose:lignin crosslinking remains to be investigated [60][61][62][63][64][65]. The recalcitrance differences observed in CAD and COMT mutants may be partially explained by reductions in lignin content.…”
Section: Nucleophilic Moieties Present In Hemicelluloses Can Participmentioning
confidence: 99%